The Profile of a Successful Speech Sound Disorder Learner (A Psycholinguistic Analysis) - Mutiara Ramadhani; Arqam; Ambo Dalle; Abdul Haris Sunubi; Magdahalena (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This study used the research subject of a 21-year-old male student with the initials AP. He was the third of four children to have a cleft lip from birth. Like most children, he attended public schools from elementary to college. Although the child has a speech disorder it does not hinder the educational process. He is known by people as a very friendly and confident child even though he was given the opportunity by his lecturer to participate in a student exchange in Jogja for four months. This study aims to find out how students deal with speech disorders. This research method uses a qualitative approach, data collection is carried out through interviews, documentation, and observation. The results of this study are: 1) Cleft lip sufferers as experienced by these students are congenital factors from birth where there are defects in the speech organs. Gaps in the gums and roof of the mouth cause nasal sounds; 2) Speech disorders can occur due to internal factors that involve genetic defects that are experienced since birth. This is thought to have occurred due to his mother having had an accident and having consumed candy station food which resulted in bleeding; 3) The shortcomings of the student are not a barrier to achieving what he aspires to. According to him, education is very important because without education it will be left behind in the era of increasingly rapid technology.